THE CORRELATION BETWEEN CHARACTER BUILDING AND PEACEFUL THINKING OF STUDENTS AT DARUSSALAM ISLAMIC BOARDING SCHOOL IN PONOROGO, EAST JAVA - Asnawir, Asnawir (AT-TALIM, 2012)
The aim of this research to identify the correlation between the character building and peaceful thinking of students at the Darussalam Islamic Boarding School (Gontor). Character building is a fundamental part of Islamic education in Darussalam Islamic Boarding School as an agenda for educating their students, like: sincerity, simplycity, self-sufficency Islamic Brotherhood and freedom. This is descriptive quantitative research which observation and questionaire were used to colected the data. Population of this research were 400 pupils. Meanwhile, the sample of 200 students were asÂ  respondents of this research (simple random sampling). This research was found that there were correlation between character building and peaceful thinking of students. The r scoreÂ  = 0,511 and r table = 1,64 and p = 0.000 , 0.05. It means, Ho rejected and recieved H1. There were correlation between character building and peaceful thinking of students.